Ectomycorrhizal Networks in the Anthropocene: From Natural Ecosystems to Urban Planning - Authier, Louise; Violle, Cyrille; Richard, Franck (Frontiers in Plant Science, 2022)
Trees acquire hydric and mineral soil resources through root mutualistic associations. In most boreal, temperate and Mediterranean forests, these functions are realized by a chimeric structure called ectomycorrhizae. Ectomycorrhizal (ECM) fungi are highly diversified and vary widely in their specificity toward plant hosts. Reciprocally, association patterns of ECM plants range from highly specialist to generalist. As a consequence, ECM symbiosis creates interaction networks, which also mediate plant–plant nutrient interactions among different individuals and drive plant community dynamics. Our knowledge of ECM networks essentially relies on a corpus acquired in temperate ecosystems, whereas the below-ground facets of both anthropogenic ECM forests and inter-tropical forests remain poorly investigated. Here, we successively (1) review the current knowledge of ECM networks, (2) examine the content of early literature produced in ECM cultivated forests, (3) analyze the recent progress that has been made in understanding the place of ECM networks in urban soils, and (4) provide directions for future research based on the identification of knowledge gaps. From the examined corpus of knowledge, we reach three main conclusions. First, the emergence of metabarcoding tools has propelled a resurgence of interest in applying network theory to ECM symbiosis. These methods revealed an unexpected interconnection between mutualistic plants with arbuscular mycorrhizal (AM) herbaceous plants, embedding ECM mycelia through root-endophytic interactions. This affinity of ECM fungi to bind VA and ECM plants, raises questions on the nature of the associated functions. Second, despite the central place of ECM trees in cultivated forests, little attention has been paid to these man-made landscapes and in-depth research on this topic is lacking. Third, we report a lag in applying the ECM network theory to urban soils, despite management initiatives striving to interconnect motile organisms through ecological corridors, and the highly challenging task of interconnecting fixed organisms in urban greenspaces is discussed. In particular, we observe a pauperized nature of resident ECM inoculum and a spatial conflict between belowground human pipelines and ECM networks. Finally, we identify the main directions of future research to make the needed link between the current picture of plant functioning and the understanding of belowground ECM networks.